Project Supply Chain Strategizies: A step towards Building Option - Syafrida Hafni Sahir; R Rosmawati; Anik Ratnawati; Dwi Ermayanti Susilo; Muprihan thaib; Noer Soetjipto; Faurani Santi Singagerda; Ari Riswanto; Dedi Putra (International Journal of Supply Chain Management, 2020)
Abstract— For organization, agencies and governments, the supply chain strategies of capital projects are the source of many challenges. For design, delivery and development as concern with time and money these kinds of projects require a design of resources and chains. This article looks at some of these themes and includes: the need for alignment between supply chain strategy and the project concept; dealing with complexity, in particular the systematic and interrelatedness within project decisions; consideration of the ambiguity implicit in all major projects. Basically it takes many years to design and delivery of a project. The final complete project expected to be useful for several years.